Inserción laboral y diversidad de género: Análisis de las barreras del liderazgo en el Distrito de Educación 13D06 Bolívar-Junín - Condoy Llamatumbi, Evelin Ibeth (2024)
The objective of this research was to analyze labor insertion, gender diversity, and the different leadership theories in the Education District 13D06 Bolívar-Junín, in order to identify effective strategies to promote equal opportunities and the empowerment of all genders in the educational labor field. The following methods were used: inductive, deductive, and analytical. In addition, bibliographic research was used to support this study with high-level scientific theoretical sources and field research to apply interview and survey techniques in the data collection process. As a result of this study, the diagnosis of the entity's leadership and gender roles reveals a significant commitment to the promotion of gender equality and labor inclusion, highlighting the implementation of measures to overcome leadership barriers and gender discrimination. In addition, gender barriers associated with conditions of inequality are based on aspects such as difficulties in opportunities for continuous training of staff without gender discrimination. Based on the data obtained, an improvement plan is presented using the 5W1H methodology. The creation and implementation of awareness and training programs on gender equality and leadership is proposed, implemented through specific talks and workshops in the 13D06 Bolívar-Junín Education District.